Parent education program “Em Equilíbrio”: Critical-reflexive study - Craveiro, Nuno (2017)
This study presents a critical reflection on the parents’ education program “Em Equilíbrio”, implemented within an inter-institutional network, following a logic of selective intervention, with the overall aim of promoting the development of parenting skills. The results obtained point to the program´s impact on key factors of parenting and family dynamics related to the prevention of antisocial behavior and child abuse. The study concludes that there is a good fit between the goals of the program and its implementation methodology. Its main asset is the promotion and involvement of the family’s formal network and the aspects to improve are the objectivity of the participants’ selection process, availability of supervision, centrality of intervention and the evaluation model.